Constructing M&A valuation: How do merger evaluation methods differ as uncertainty and controversy vary? - Hyoung Goo Kang; Wonseok Woo; Richard M. Burton; Will Mitchell (Journal of Organization Design, 2018)
We investigate the idea that firms' choices of M&A evaluation methods are influenced by two socio-political factors that arise in the behavioral theory of the firm-uncertainty and controversy. In doing so, we investigate boundary conditions between arguments that expect firms to use financial analysis such as net present value as the primary tool and arguments that emphasize different forms of socio-political processes, often supplemented by subsequent financial analysis. We undertake exploratory qualitative analysis of multiple cases at a Korean chaebol, complemented by interviews with global deal-makers. The analysis highlights four approaches to M&A evaluation that vary with combinations of uncertainty and controversy: desktop valuation based on financial analysis, capability design using scenario-planning and goal-setting techniques, issue lists that identify conflicting goals, and storytelling methods that attempt to articulate compelling logics for a deal. The results suggest that M&A values are sometimes endogenously created as a result of the method that firms use to evaluate a deal. The work addresses and links two audiences: First, M&A scholars who often do not engage with the idea of socio-political processes but are open to the idea that there are important boundary conditions to the frameworks that are relevant when one does not do so. Second, scholars who do regularly engage with the idea of socio-political processes and are intrigued with determining how social constructs such as uncertainty and controversy will shape particular types of decisions.
Keywords: 650; Mergers and acquisitions; Valuation; Uncertainty; Controversy; Capital budgeting